A two-dimensional integrated complexity factors assessment framework for infrastructure project performance and phases in Malaysia / Akhtarul Norfaiza Che Nen - Che Nen, Akhtarul Norfaiza (2022)
Complex infrastructure projects, such as highways, bridges, ports, airports, and mass transit, have been characterised as large-scale capital expenditure, longer completion period, require specific technical and more process complexity levels. Their complexity level regardless of their size, cost, longer duration, and less quality that expected prone to three main consequences during construction including, several design changes, land acquisition, and delaying approval process. Those consequences are warranted an ineffective tool for assessing and managing that complexity factors. So far, several empirical studies pertaining to complex factors reported on weak impact of tripartite project performance (time, cost, and quality) during triple project phases. Hence the project complexity tools still lacking and waiting to be explore either qualitative or quantitative measures throughout the project phases (pre-construction, construction, & post-construction).